(untitled) (Experimental biology, 2015)
Morphological structure of reproductive organs for 3 species genus Chamaedorea Willd. was studded at first. Changing in morphological structure depend from specific belonging of plants. Male plants Chamaedorea oblongata decreased of length of lateral axis, Chamaedorea pochutlensis – increased the parameter. Decreasing of length all inflorescence are touched for female plants Chamaedorea tepejilote.